Optimal frame rate to evaluate boar sperm kinematic with a CASA-Mot system - Barquero, Vinicio; Víquez, Luis; Calderón Calderón, Josué; Valverde, Anthony (Agronomía Mesoamericana, 2021)
Introduction. Motility is the most used seminal quality indicator, therefore, it is necessary to determine an adequate frame rate (FR) to standardize kinetic analysis with computerized semen analysis equipment (CASA-Mot) and reduce variability between laboratories, which will improve the number of seminal doses and their quality for the swine industry based on artificial insemination (AI). Objective. To determine the optimal frame rate frequency on boar sperm kinetics using a commercial CASA-Mot system and to analyze the distribution of sperm subpopulations with the optimal FR. Materials and methods. Twenty seminal doses of ten Pietrain boars (Sus scrofa domestica) were used. The experimental period was between February and July 2017. The CASA-Mot system (ISAS®v1) was used with ISAS® D4C20 counting chambers preheated to 37 °C. The video capture time was two seconds. Results. The frame rate affected the sperm kinetic parameters, except for the rectilinear velocity (VSL), because it did not represent a FR-dependent behavior. The other variables presented significant alterations when changing their FR, and curvilinear velocity (VCL) and average path velocity (VAP) were the most sensitive values to the change. Three principal components (PC) defined by patterns of motility, progressiveness and oscillation were obtained, where the PC1 (velocity-undulation) was the most influential since it represented 51.34 % and 55.08 % of the total explained variance for 25 and 200 fps (frames per second), respectively. Conclusion. The optimal frame rate to analyze sperm kinematics variables in boar semen with a CASA-Mot system was 200 fps. A lower frame rate causes errors in the sperm trajectory estimation. The sperm subpopulation distribution changes according to the frame rate used. It is necessary to establish an analysis protocol to homogenize the results.